2015
DOI: 10.1039/c4sc02022g
|View full text |Cite
|
Sign up to set email alerts
|

Combining luminescence spectroscopy, parallel factor analysis and quantum chemistry to reveal metal speciation – a case study of uranyl(vi) hydrolysis

Abstract: The sensitive excitation of uranyl(vi) hydrolysis species in the UV (180 to 370 nm) is due to ligand-to-metal charge transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 76 publications
(84 reference statements)
5
81
1
Order By: Relevance
“…Cytochrome c3 has a mid-point redox potential near −300 mV versus SHE (standard hydrogen electrode) at 25°C (Niki et al, 1984), while the U(VI)-U(IV) couple has a mid-point potential of +334 mV versus SHE of dissolved inorganic carbon (DIC) and with a wide range of pH is of paramount importance for understanding microbial reduction of U(VI), since different U(VI) species could have different susceptibilities of being reduced based on their bioavailability. A decrease in U(VI) reduction rate with increasing DIC concentration, along with sensitivity towards pH, has been well documented in the literature (Belli et al, 2015;Bernhard, Geipel, Brendler, & Nitsche, 1998;Brooks et al, 2003;Croteau, Fuller, Cain, Campbell, & Aiken, 2016;Drobot et al, 2015;Guillauont et al, 2003;Jones et al, 2015;Sheng & Fein, 2014;Ulrich et al, 2011).…”
Section: Electron Flow and Speciationmentioning
confidence: 70%
See 1 more Smart Citation
“…Cytochrome c3 has a mid-point redox potential near −300 mV versus SHE (standard hydrogen electrode) at 25°C (Niki et al, 1984), while the U(VI)-U(IV) couple has a mid-point potential of +334 mV versus SHE of dissolved inorganic carbon (DIC) and with a wide range of pH is of paramount importance for understanding microbial reduction of U(VI), since different U(VI) species could have different susceptibilities of being reduced based on their bioavailability. A decrease in U(VI) reduction rate with increasing DIC concentration, along with sensitivity towards pH, has been well documented in the literature (Belli et al, 2015;Bernhard, Geipel, Brendler, & Nitsche, 1998;Brooks et al, 2003;Croteau, Fuller, Cain, Campbell, & Aiken, 2016;Drobot et al, 2015;Guillauont et al, 2003;Jones et al, 2015;Sheng & Fein, 2014;Ulrich et al, 2011).…”
Section: Electron Flow and Speciationmentioning
confidence: 70%
“…The conventional thinking is that free UO 2 2+ and its mono-nuclear complexes with hydroxides and carbonates are bioavailable to microorganisms (Tutem, Apak, Turgut, & Apak, 1991). Poly-nuclear complexes are known to have lesser cell permeability and, hence, may have lower bioavailability (Bernhard et al, 1998;Croteau et al, 2016;Drobot et al, 2015;Guillauont et al, 2003;Jones et al, 2015;Kulkarni, Misra, Gupta, Ballal, & Apte, 2016). In addition, adsorption of U(VI) to colloidal or particulate ligands should render it even less bioavailable (Du et al, 2011).…”
Section: Electron Flow and Speciationmentioning
confidence: 99%
“…Later, we have found that a similar approach was used for uranyl hydroxo-complexes by Drobot et al [106]. We also look for quantum chemistry to interpret the experimental results.…”
Section: -2(4 2(-mentioning
confidence: 99%
“…Visible on the absorption and emission bands are the vibronic progression arising from strong coupling of the ground state Raman active symmetric vibrational O=U=O (ν 1 ) mode with the 3 Π u electronic triplet excited state. Time resolved studies allow sometimes complex speciation in water to be deconvoluted [7], whilst in non-aqueous media the positions of the emission maxima and lifetimes can be used as electronic and structural probes. For instance in the family of complexes trans-[UO 2 X 2 (O=PPh 3 ) 2 ] (X = Cl, Br, I) the photoluminescent properties do not vary [8], but for the compounds trans-[UO 2 Cl 2 L 2 ] (L = Ph 3 P=NH, Ph 3 P=O and Ph 3 As=O) a red shift in the O yl ÑU LMCT band is observed, in line with the increased donor strength of the ligand [9].…”
Section: Introductionmentioning
confidence: 99%